Adult Education Faculty and Programs in North America: Faculty Background, Work, and Satisfaction - Elizabeth J. Tisdell; Robin Redmon Wright; Edward W. Taylor; Perdeta Bush; Anne Greenawalt (Adult Education Research Conference, 2014)
Through a textual analysis of websites of Adult Education Graduate Programs and a quantitative survey of North American Adult Education faculty, this study examined: background information about Adult Education faculty and programs; the nature of faculty work interests, motivations and satisfaction; and involvement with the Commission of Professors of Adult Education.